Effects of a self-care behavior development program for Diabetes Mellitus patients at Kut Chum district, Yasothon province - Suwannasri, Jirawan; Iemsawasdikul, Warinee; Potisupsuk, Chuenjit (Thai Journal of Nursing, 2020)
The objectives of this quasi-experimental research were to compare self-care behavior, blood sugar and blood pressure of an experimental group before and after experiment, and after experiment between the experimental group and the comparison group. The sample of 70 Diabetes Mellitus patients who could not control blood sugar, attended at the chronic disease clinic in Non Mi and Phon Ngam subdistrict health promoting hospital, Kut Chum district, Yasothon province, were selected by the purposive sampling technique and equally divided into the experimental group and the comparison group using matched-pairs method. The research tools were: 1) the Self-care Behavior Development Program based on Orem’s self-care theory, 2) a questionnaire on general data and self-care behavior, its CVI was 0.96 and Cronbach’ s alpha coefficient was 0.92, 3) glucometer and digital sphygmomanometer. Data were analyzed by descriptive statistics, t-test, Wilcoxon Matched -Pairs Signed rank test, and Mann-Whitney U test. The results found as follows. 1) After experiment, overall self-care behaviors of the experimental group was significantly higher than before experiment and increase more than the comparison group (p < .05). Self-care behaviors on the subparts of eating and exercise of the experimental group were significantly higher than before experiment and the comparison group, but there was no significant difference on the subpart of taking medicine. 2) After experiment, blood sugar from finger tip and HbA1C of the experimental group were significantly lower than before experiment and the comparison group (p < .05). Systolic blood pressure of the experimental group was significantly lower than before experiment, but it was not significantly different from the comparison group. Diastolic blood pressure of the experimental group was significantly higher than before experiment, but it was not significantly different from the comparison group (p < .05).